Synthesis of NiO/Ni Electrocatalyst at Different pH Values and the Application for Electrochemical Degradation of Textile Waste - Ni Made Wiratini (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
An electrocatalyst is a material that exhibits catalytic activity for electrochemical reactions. The electrocatalytic properties within electrochemical cells can be enhanced by modifying the electrode through an electrodeposition process. Therefore, this study aimed to synthesize NiO/Ni electrocatalyst using the electrodeposition method at pH values of 8, 10, and 12. The NiO/Ni generated was applied in the electrochemical degradation of textile waste under specific operating conditions, including pH 4, NaCl concentration of 0.05 M, DC voltage of 9 volts, and varying degradation times of 60, 120, 180, and 240 min. Based on the results, the XRD diffractograms revealed the presence of NiO peaks at 2θ = 43.5°, 63.1°, and 75.4°, and Ni peaks at 2θ = 51.9°. SEM-EDX analysis showed that NiO/Ni was deposited on the graphite surface in the form of spheres and granules. FTIR indicated the presence of Ni−O bonds at 501 cm−1, and GSA demonstrated that NiO/Ni exhibited mesoporous properties. The NiO/Ni at pH 10 had the highest surface area, pore volume, and current response compared to graphite, as well as the electrocatalyst produced at pH 8 and 12. Additionally, the electrochemical degradation of textile waste using NiO/Ni at pH 10 led to the highest reduction in absorbance efficiency, chemical oxygen demand (COD), and ammonia, with respective values of 96.80, 96.15, and 87.34%. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).